MoS2 nanoparticles grown on carbon nanomaterials for lubricating oil additives - Kuiliang Gong; Wenjing Lou; Gaiqing Zhao; Xinhu Wu; Xiaobo Wang (Friction, 2020)
Abstract In this study, the nanocomposites of MoS2 nanoparticles (NPs) grown on carbon nanotubes (MoS2@CNT), graphene (MoS2@Gr), and fullerene C60 (MoS2@C60) were synthesized, characterized, and evaluated for potential use as lubricant additives. By using the benefit of the synergistic effect between MoS2 and carbon nanomaterials (CNMs), these nanocomposites can be well dispersed in polyalkylene glycol (PAG) base oil and show superior stability compared with pure MoS2 NPs. Moreover, the dispersions of MoS2@CNT, MoS2@Gr, and MoS2@C60 added in PAG have noticeably improved friction reducing and antiwear (AW) behaviors at elevated temperature for comparison with that of PAG and PAG containing CNT, Gr, C60, and MoS2 NPs, respectively. The enhanced lubricating properties of these nanocomposites were also elucidated by exploring the tribofilm formed on the disc.